MicroRNA Regulation of Endothelial Junction Proteins and Clinical Consequence - Yugang Zhuang; Hu Peng; Victoria Mastej; Weiguo Chen (Mediators of Inflammation)
Cellular junctions play a critical role in structural connection and signal communication between cells in various tissues. Although there are structural and functional varieties, cellular junctions include tight junctions, adherens junctions, focal adhesion junctions, and tissue specific junctions such as PECAM-1 junctions in endothelial cells (EC), desmosomes in epithelial cells, and hemidesmosomes in EC. Cellular junction dysfunction and deterioration are indicative of clinical diseases. MicroRNAs (miRNA) are ~20 nucleotide, noncoding RNAs that play an important role in posttranscriptional regulation for almost all genes. Unsurprisingly, miRNAs regulate junction protein gene expression and control junction structure integrity. In contrast, abnormal miRNA regulation of junction protein gene expression results in abnormal junction structure, causing related diseases. The major components of tight junctions include zonula occluden-1 (ZO-1), claudin-1, claudin-5, and occludin. The miRNA regulation of ZO-1 has been intensively investigated. ZO-1 and other tight junction proteins such as claudin-5 and occludin were positively regulated by miR-126, miR-107, and miR21 in different models. In contrast, ZO-1, claudin-5, and occludin were negatively regulated by miR-181a, miR-98, and miR150. Abnormal tight junction miRNA regulation accompanies cerebral middle artery ischemia, brain trauma, glioma metastasis, and so forth. The major components of adherens junctions include VE-cadherin, β-catenin, plakoglobin, P120, and vinculin. VE-cadherin and β-catenin were regulated by miR-9, miR-99b, miR-181a, and so forth. These regulations directly affect VE-cadherin-β-catenin complex stability and further affect embryo and tumor angiogenesis, vascular development, and so forth. miR-155 and miR-126 have been shown to regulate PECAM-1 and affect neutrophil rolling and EC junction integrity. In focal adhesion junctions, the major components are integrin β4, paxillin, and focal adhesion kinase (FAK). Integrin β4 has been regulated by miR-184, miR-205, and miR-9. Paxillin has been regulated by miR-137, miR-145, and miR-218 in different models. FAK has been regulated by miR-7, miR-138, and miR-135. Deregulation of miRNAs is caused by viral infections, tumorigenesis, and so forth. By regulation of posttranscription, miRNAs manipulate junction protein expression in all cellular processes and further determine cellular fate and development. Elucidation of these regulatory mechanisms will become a new alternative therapy for many diseases, such as cancers and inflammatory diseases.